Coalition government and electoral accountability - Fisher, S; Hobolt, S (Elsevier, 2010)
Single-party governments are commonly thought to be more clearly responsible for government policy than coalition governments. One particular problem for voters evaluating coalition governments is how to assess whether all parties within a coalition should be held equally responsible for past performance. As a result, it is generally accepted that voters are less likely to hold coalition governments to account for past performance. This article uses data from the Comparative Study of Electoral Systems project to assess whether and how the composition of coalition governments affects the way in which people use their votes to hold governments to account, and which parties within coalitions are more likely to be held to account for the government's past performance.